1.3 μm passively Q-switched mode-locked laser with Fe3O4 nanoparticle saturable absorber. (9th November 2020) - Zhang, Huaiwei; Peng, Jiying; Yao, Jianquan; Yang, Xiangpeng; Li, Decai; Zheng, Yi
Abstract: Fe3 O4 nanoparticles (FONP) are made into saturable absorbers and assembled into the resonant cavity, for the first time, and passively Q-switched mode-locked (QML) pulse output is realized in a 1.3 μ m all-solid-state laser. When the pump power increases to 8 W, the repetition frequency of the Q-switched pulse increases from 47 kHz to 116 kHz, the pulse width changes from 1.137 μ s to 767 ns, and the corresponding single pulse energy is 1.2 μ J. At the same time, the passively QML operation was observed on the oscilloscope, with a pulse repetition frequency of 154.5 MHz and a pulse width of 660 ps. Our experiments demonstrate that FONP exhibits good nonlinear optical characteristics in the 1.3 μ m waveband, and has the potential to realize giant ultrashort and multiwavelength tunable pulse output in all-solid-state pulsed lasers.